Phase transitions in thermally annealed films of Alq3 - Baldacchini, G.; Chiacchiaretta, P.; Pode, R.B.; Vincenti, M.A.; Wang, Q.-M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Organic light emitting devices have been so very much improved lately that they are being widely applied fordisplays and lighting. Among many improving technologies, annealing processes in different atmospheres affect greatly their performance, for instance when the active material is the small molecule Alq3. In particular, a significant increase of the photoluminescence is observed in thin films of this molecule between 150 and 180 °C, before the physical destruction of the films occurs at higher temperatures. This phenomenon is attributed to a phase transitiontowards a novel morphological aggregation of the molecules in the film, which proved to be a much improvedoptical material for luminescent applications, and which seems common to other molecules as well.